Analysis of the Impact of Frontliner Employee Performance Assessment at PT. Bank Rakyat Indonesia (Persero), Tbk. KC Jakarta Tanjung Priok - Anam, Khoirul (Inovbook Publications, 2024)
Performance appraisal of frontliner employees at PT Bank Rakyat Indonesia (Persero), Tbk. Kc Jakarta Tanjung Priok has a significant impact on employee development and performance. Through analysis, it can be seen that performance appraisals provide clear feedback, motivate employees to improve their performance, strengthen teamwork, and drive process and system improvements. Supporting factors such as transparent appraisal systems, strong management support, sustainable reward systems, and effective communication contribute to the success of performance appraisals. However, there are also challenges such as subjectivity in appraisals and employee resistance to the appraisal process that need to be overcome. With attention to these constraints and maximization of supporting factors, PT Bank Rakyat Indonesia (Persero), Tbk. Kc Jakarta Tanjung Priok can ensure that performance appraisal of frontline employees becomes an effective tool in achieving organizational goals and overall employee development.